2004
DOI: 10.1242/dev.01260
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of gene expression by Brn3a in developing sensory ganglia

Abstract: Mice lacking the POU-domain transcription factor Brn3a exhibit marked defects in sensory axon growth and abnormal sensory apoptosis. We have determined the regulatory targets of Brn3a in the developing trigeminal ganglion using microarray analysis of Brn3a mutant mice. These results show that Brn3 mediates the coordinated expression of neurotransmitter systems, ion channels, structural components of axons and inter- and intracellular signaling systems. Loss of Brn3a also results in the ectopic expression of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 39 publications
(38 reference statements)
7
95
1
1
Order By: Relevance
“…However, HNF3-␤/ FOXA2 is not expressed in TG and DRG throughout the development (Rausa et al, 1997), suggesting there are other transcription factors regulating the expression of Advillin. A previous study by Eng et al (2004) showed Advillin mRNA is reduced in Brn3a-null mice, suggesting the POU-domain transcription factor Brn3a may also control the expression of Advillin, although we did not identify any POU-domain factor binding site in the immediate genomic region adjacent to Advillin. It could well be that enhancer elements located distantly regulate Advillin expression.…”
Section: Discussioncontrasting
confidence: 81%
“…However, HNF3-␤/ FOXA2 is not expressed in TG and DRG throughout the development (Rausa et al, 1997), suggesting there are other transcription factors regulating the expression of Advillin. A previous study by Eng et al (2004) showed Advillin mRNA is reduced in Brn3a-null mice, suggesting the POU-domain transcription factor Brn3a may also control the expression of Advillin, although we did not identify any POU-domain factor binding site in the immediate genomic region adjacent to Advillin. It could well be that enhancer elements located distantly regulate Advillin expression.…”
Section: Discussioncontrasting
confidence: 81%
“…50 Brn-3a has a possible role in the transcriptional regulation of at least three VGSCas (Nav1.7, Nav1.8 and Nax) since their levels were decreased in the sensory neurons of Brn-3a knockout mice. 34 This supports a role for Brn3a in upregulating Nav1.7 expression, as demonstrated here. Brn-3a may therefore represent the second transcription factor that regulates VGSCa mRNA levels and an important determinant of Nav1.7 expression in CaP in vivo.…”
Section: Upregulation Of Brn-3a[s] In Cap and Role In Growthsupporting
confidence: 84%
“…27,31-33 Brn-3a is a potential VGSC transcription factor given that mRNA levels of several VGSC a-subunit (VGSCa) genes, including SCN9A/ Nav1.7, which is specifically upregulated in CaP, 29 are significantly altered in the sensory neurons of Brn-3a knockout mice. 34 Several other established Brn-3 target genes, particularly those with roles in apoptosis such as Bcl-2, Bcl-x, Bax and Hsp27, also exhibit altered expression in CaP. [35][36][37] In summary, (i) Brn-3 transcription factors play an important role in normal cellular (neuronal/NE) differentiation; (ii) their expression is altered in other tumours of reproductive (and NE) origin; and (iii) known Brn-3 target genes exhibit altered expression in CaP.…”
Section: Introductionmentioning
confidence: 99%
“…The position of ectopic sympathetic neurons in the ventral trunk between the dorsal aorta and the limb correlated with the expression pattern of 2 secreted proteins that promote sympathetic differentiation, BMP4 and BMP7 (24). In contrast, the Tuj1-positive ectopic clusters in dorsolateral locations did not express TH; instead, they expressed the sensory markers Isl1 (25) and Brn3a (26), confirming that they contained sensory neurons (arrows in Fig. 6 B,D, F, and H, respectively; 4/5 and 4/4 cases, respectively).…”
Section: Resultsmentioning
confidence: 87%